Natural Selection and Genetic Drift: Neutral and adaptive genetic variability of hatchery versus wild populations in brown trout Salmo trutta - Tamara Schenekar (Frontiers in Marine Science, 2015)
Genetic drift and natural selection are two of the major forces shaping the genetic makeup of a population. Genetic drift reduces genetic variability due to the random loss of alleles during the transition from one generation to the next one. The smaller the population, the stronger genetic drift is. Natural selection favors the spread of specific alleles within a population over time, namely those alleles that are beneficial in the specific environment of this population. Individuals that carry alleles that are less advantageous have a lower probability to survive and reproduce. For establishing a captive population, very often, only a small number of individuals are taken and the number breeding individuals used to maintain the population is limited, thus increasing the amount of genetic drift. On the other hand, the drastically different environment in captivity (artificial diet, higher individual density, altered pathogen pressure, etc.) may favor alleles that are maladaptive for individuals when they are released back in the wild, e.g. for stocking measures. We screened both, neutral and adaptive genetic markers, in order to assess the relative importance of genetic drift and selection pressure on wild and hatchery populations of Austrian brown trout. We confirm a strong positive selection pressure on an adaptive locus of the Major histocompatibility Complex (MHC), whereas the signal of this selection pressure was more pronounced in hatchery populations. This may either stem from stronger genetic drift in wild populations due to smaller effective population sizes or a stronger directional selection in these wild populations, whereby only particular genetic variants proved to be adaptive in each specific environment. Therefore, the alleles arising from the hatchery selection regime may be detrimental in the wild, which can lead to lower survival rates of stocked fish in wild environments.